(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
One of the fundamental difficulties of Latvia’s economical development is related to state’s dependency from the import of fuel energy resources and weak use of the local resources: the main fuel of the local boiler houses using fuel oil imported from CIS countries; local wood and peat used in heat production constitutes no more than 25%. In the same time it is needed to take in account the new regulations of EU against fuel oil having concentration more than 1% sulphur. These issues make country to search for new fuel materials and approaches to raise effectiveness of local energy resources.